2018
DOI: 10.1038/s41388-018-0613-5
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-11 regulates the tumour suppressor function of STAT1 in a murine model of colitis-associated carcinogenesis

Abstract: Murine inflammatory caspase-11 has an important role in intestinal epithelial inflammation and barrier function. Activation of the non-canonical inflammasome, mediated by caspase-11, serves as a regulatory pathway for the production of the pro-inflammatory cytokines IL-1β and IL-18, and has a key role in pyroptotic cell death. We have previously demonstrated a protective role for caspase-11 during dextran sulphate sodium (DSS)-induced colitis, however the importance of caspase-11 during colorectal tumour devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Survival analysis have revealed that lower NLRP1 are correlated with a shorter patient survival period 69 . In addition, compared to wild-type (WT) littermates, Casp11 −/− mice are highly vulnerable to the AOM/DSS model of CAC 70 . GSDMA was not expressed in normal colorectal epithelial cells but was gradually overexpressed in carcinoma cells, while GSDMD exhibited the opposite trend 71,72 .…”
Section: Role Of Pyroptosis In Tumorigenesis and Metastasismentioning
confidence: 99%
“…Survival analysis have revealed that lower NLRP1 are correlated with a shorter patient survival period 69 . In addition, compared to wild-type (WT) littermates, Casp11 −/− mice are highly vulnerable to the AOM/DSS model of CAC 70 . GSDMA was not expressed in normal colorectal epithelial cells but was gradually overexpressed in carcinoma cells, while GSDMD exhibited the opposite trend 71,72 .…”
Section: Role Of Pyroptosis In Tumorigenesis and Metastasismentioning
confidence: 99%
“…In their study, Flood et al reported heightened susceptibility and exacerbated tumor growth in Casp11 −/− mice compared to their littermate controls. The enhanced tumor burden was associated with reduced levels of both IL-1β and IL-18 which resulted in reduced STAT1 signaling and sub-optimal anti-tumor type I immunity (236). Given that IL-1 cytokines derived from activated inflammasomes evidently play a fundamental role in determining the severity of various gastro-intestinal disorders, consideration must also be given to the composition of the commensal microbiota in these mouse strains.…”
Section: Inflammasomes In Ibdmentioning
confidence: 99%
“…Accumulating evidence has revealed that inflammasomes are involved in the pathological processes of different tumors [14,30,31], but the specific molecular mechanisms remained incompletely elucidated. In this study, we identified different expression patterns and prognostic characteristics of IRGs among 10 cancers.…”
Section: Discussionmentioning
confidence: 99%